PENGARUH PEMAHAMAN MOTIVASI DAN TINGKAT DISIPLIN KERJA TERHADAP KINERJA TENAGA KERJA PADA KANTOR KECAMATAN RUMPIN KABUPATEN BOGOR - Putri Maulidia; Priehadi Dhasa Eka (Jurnal Menara, 2025)
This research aims to determine the effect of motivation understanding and work discipline level on employee performance at Rumpin Sub-District Office, Bogor Regency. The research method used is a quantitative approach with a survey technique through questionnaires distributed to the for entire population of 66 employees. The for results of simple regression analysis show that motivation understanding has a positive and significant effect on performance with the regression equation Y = 27.691 + 0.255 X1, t value of 8.292 > t table 1.669, and significance value of 0.000 < 0.01. Meanwhile, work discipline also has a positive and significant effect on performance with the regression equation Y = 15.936 + 0.546 X2, t value of 4.472 > t table 1.669, and significance value of 0.000 < 0.01. The multiple regression analysis shows that motivation understanding and work discipline simultaneously have a significant effect on performance with the regression equation Y = 14.776 + 0.075 X1 + 0.519 X2, F value of 14.936 > F table 3.140, and significance value of 0.000 < 0.05. Thus, it can be concluded that motivation understanding and work discipline have positive and significant effects both partially and simultaneously on the performance of employees at Rumpin Sub-District Office, Bogor Regency.